1996
DOI: 10.3109/10826089609045827
|View full text |Cite
|
Sign up to set email alerts
|

Crack Use in Sa¯o Paulo

Abstract: Documented crack use emerged in São Paulo, Brazil, from 1991 onward. Therefore, it is a recent behavior among drug users. The present work draws a profile of São Paulo crack users, employing an ethnographic approach. Twenty-five crack users were interviewed on selected social and demographic characteristics, on the drug itself and its consumption, and on the consequences of this use. Crack cocaine is harmful for the user, leading within a short period to a condition of dependence. The crack users reported ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1
33

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 16 publications
2
33
1
33
Order By: Relevance
“…Because of the effects of crack, it was rare for users to consume it just once: they kept on using it until they were physically, psychologically or fi nancially wrecked. 17,18 As seen in the United States, 10,11,20 users' thoughts were focused on crack consumption, such that sleep, food, affection, sense of responsibility and survival lost their meanings. Another paper by Nappo et al 18 showed that, because of users' cravings for the drug and their lack of money, they found themselves obliged to take part in illegal activities (drug traffi cking, robbery and assault).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the effects of crack, it was rare for users to consume it just once: they kept on using it until they were physically, psychologically or fi nancially wrecked. 17,18 As seen in the United States, 10,11,20 users' thoughts were focused on crack consumption, such that sleep, food, affection, sense of responsibility and survival lost their meanings. Another paper by Nappo et al 18 showed that, because of users' cravings for the drug and their lack of money, they found themselves obliged to take part in illegal activities (drug traffi cking, robbery and assault).…”
Section: Introductionmentioning
confidence: 99%
“…8 At fi rst in Brazil, this controlled use was not detected among crack users. 17,18 The use of crack has persisted in Brazil, b despite the severe problems that it causes to those who consume it, such as marginality, criminality and devastating physical and psychological effects. Thus, it is suspected that the culture of crack use may have undergone changes since the time when it was fi rst described in the city of São Paulo, published 11 years ago.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crack-cocaine users' profile was first investigated in 1989, demonstrating that use was made mostly by men younger than 30, unemployed, with low purchasing power and education 16 . Similarly, Health Surveys published later portray higher percentage of use in males 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Além das pesquisas com diferentes populações, as implicações econômicas também têm sido discutidas, considerando que o uso de drogas é um problema de saúde pública e apresenta um grande impacto econômico à sociedade (Moraes, Campos, Figlie, Laranjeira, & Ferraz, 2006). Outros focos importantes de estudos têm sido o perfil dos usuários (Carlini et al, 2007;Duailibi, Ribeiro, & Laranjeira, 2008;Horta, Horta, Rosset, & Horta, 2011;Nappo, Galduróz, & Noto, 1996;Oliveira & Nappo, 2008) e as diferentes formas de tratamento (Carrol, 2004;Carrol et al, 1994;Focchi, Leite, Laranjeira, & Andrade, 2001;Karila et al, 2011;Rangé & Marlatt, 2008).…”
unclassified